PROBLEMS OF DETERMINATION AND CONTINUATION OF THE RESOURCE OF SECURITY OPERATION OF MAIN PIPELINES - Martyniuk, R. T.; Shyian, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The scale of the Ukrainian pipeline system, the large variety of complex hydrogeological conditions for pipe laying, and a significant number of those that have worked, predetermine a particular attitude to the work to ensure their reliable functioning. The continuation of the resource for the safe exploitation of steel structures has now become acute in all industrialized countries. For Ukraine, the importance of their solution is due to a decrease in the volumes of production of metal structures to replace those that are being decommissioned. This primarily concerns the objects of energy, oil and gas pipelines, the chemical industry, land and air transport and construction.